Monitoring financial risk and earnings manipulation across Malaysia, Thailand and Indonesia / Saunah Zainon ... [et al.] - Zainon, Saunah; Jamaludin, Zakiyyah; Mohd Sali@Salleh, Kharudin; Md Nawi, Sofwah; Mokhtar, Nurkhairany Amyra; Ahmad, Syahrul Ahmar (Accounting Research Institute (ARI), 2022)
This paper discusses the significance of mean difference in free cash flow, leverage, as well financial distress between Malaysia, Thailand, and Indonesia. It involved 582 samples from Bursa Malaysia, Stock Exchange of Thailand, and Indonesia Stock Exchange on an annual basis commencing from 2015 to 2017. The purpose of this study was to determine whether the significance of variables towards earnings manipulations (by proxy of discretionary accruals) within the countries can be used to propose a new regulation that focuses more towards reducing the earning manipulation within the firm, as results might be helpful for firms in the near future. Moreover, the study aimed to identify which firm within these three countries wholly manipulated earnings more than the other. The significance difference of the of earning manipulation for the 3 countries was investigated. The descriptive statistics tells that Indonesia had the highest debt compared to two other countries. Results from one-way ANOVA, which was used to determine if there was a significant difference for free cash flow, leverage, and financial distress respectively, across these countries, showed that there were mean significant differences for all three variables.